Encapsulated pyridazine Cr(III) complexes prepared from biosorbents supported in zeolites - Figueiredo, Hugo (2005)
The encapsulation of a pyridazine Cr(III) complex was prepared from a robust biosorption system consisting of a bacterial biofilm supported on NaY or NaX zeolites. The maximum removal efficiency was 20% for Cr in both systems based in NaY or NaX. The bacterial biofilm, Arthrobacter viscosus, supported on the zeolite reduce Cr(VI) to Cr(III). The Cr(III) is retained in the zeolite by ion exchange. These occluded complexes were characterized by chemical analysis, spectroscopic methods (FTIR and UV/Vis) and surface analysis (DRX). The various techniques of characterization used show that the Cr(III) complex was effectively encapsulated in the zeolite and this process does not modified the morphology and structure of the NaY/NaX zeolites. These materials have potential applications in heterogeneous catalysis in mild conditions.